Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-27176-w
|View full text |Cite
|
Sign up to set email alerts
|

BAF complexes drive proliferation and block myogenic differentiation in fusion-positive rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is a pediatric malignancy of skeletal muscle lineage. The aggressive alveolar subtype is characterized by t(2;13) or t(1;13) translocations encoding for PAX3- or PAX7-FOXO1 chimeric transcription factors, respectively, and are referred to as fusion positive RMS (FP-RMS). The fusion gene alters the myogenic program and maintains the proliferative state while blocking terminal differentiation. Here, we investigated the contributions of chromatin regulatory complexes to FP-RMS tumor mainten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 90 publications
0
21
0
Order By: Relevance
“…To broadly affect SWI/SNF function in MRT we treated the G401 cell line with commercially available proteolysis targeting chimera (PROTAC) degrader, ACBI1 [ 16 18 ] that targets the SWI/SNF ATPases, BRG1 and BRM, as well as the pBAF subunit, PBRM1 (polybromo 1). Treatment with 250 nM ACBI1 leads to a rapid reduction in levels of BRG1 and PBRM1 as early as 1 h following treatment, while not affecting protein levels of MYC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To broadly affect SWI/SNF function in MRT we treated the G401 cell line with commercially available proteolysis targeting chimera (PROTAC) degrader, ACBI1 [ 16 18 ] that targets the SWI/SNF ATPases, BRG1 and BRM, as well as the pBAF subunit, PBRM1 (polybromo 1). Treatment with 250 nM ACBI1 leads to a rapid reduction in levels of BRG1 and PBRM1 as early as 1 h following treatment, while not affecting protein levels of MYC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…And ACBI1 treatment only impacted cell growth of cancer cell lines known to depend on BRG1/BRM function—an effect that could be blocked by addition of a competing bromodomain ligand—demonstrating notable specificity and selectivity in the action of ACBI1 [ 16 ]. Subsequent analyses using this commercially available degrader as both a biological tool compound [ 18 ] and small molecule therapeutic [ 17 ] have been reported, expanding the use of this selective degrader as a means to inactivate SWI/SNF function rapidly. This well-characterized molecule was key to uncovering the novel findings in this study as chemical degradation of BRG1 allowed for analysis of rSWI/SNF function at much earlier timepoints than previously used when targeting rSWI/SNF [ 5 , 6 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic ability of this chimeric TF to alter repressive chromatin states enables a network of chromatin interactions in FP-RMS, including looping at the MYOD1 and SOX8 gene loci to promote positive autoregulation of tumor-specific gene activation [ 18 ]. The clinical molecule entinostat, which inhibits the function of histone-H3 deacetylases, systematically alters chromatin looping in FP-RMS preceding myogenic differentiation and loss of tumor proliferation [ 9 , 19 ]. With spike-in quantification of HiChIP (AQuA-HiChIP), we observed that entinostat treatment has immediate-early effects to augment chromatin looping in FP-RMS, deregulating gene expression [ 9 , 18 ].…”
Section: Main Textmentioning
confidence: 99%
“…Proteomics quantification experiments enable monitoring relative abundances of thousands of proteins in biological samples. Most studies use parallel-group designs, where one or many treatment groups are compared to the control group (Leeuw et al 2022; Laubscher et al 2021). More recently, more complex experimental designs with an increasing number of samples are studied, e.g., factorial designs and longitudinal studies (time series), sometimes with repeated measurements on the same subject (Tan et al 2022; Meier-Abt et al 2021).…”
Section: Introductionmentioning
confidence: 99%